Effects of encapsulated niacin on metabolism and production of periparturient holstein cows - Barry J. Bradford; Laman K. Mamedova (Kansas Agricultural Experiment Station Research Reports, 2009)
Niacin (nicotinic acid) can suppress lipolysis, but responses to dietary niacin have been inconsistent in cattle. A widely used commercial feed additive, niacin is thought to reduce heat stress and decrease postpartum plasma nonesterified fatty acid (NEFA) concentration. Raw niacin has poor stability in the rumen, however, and it is estimated that only 5% is bioavailable. Recently, an encapsulated niacin (EN) product with an estimated 40% bioavailability became commercially available, but its effects on health and metabolism in transition cows have not been tested previously. Twenty-two Holstein cows were used in a study beginning 21 days before expected calving; cows were assigned to the EN treatment (24 g/day) or control group until 21 days postpartum. Results showed that EN decreased peak plasma NEFA and ketone concentrations after calving but also caused a 9 lb/day decrease in dry matter intake during the final 4 days before calving in multiparous cows. These results indicate that a high dose of EN can decrease postpartum plasma NEFA and ketones but also may decrease prepartum dry matter intake.; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Dairy; Lipolysis; Feed intake; Milk yield; NEFA; Niacin